ANALYSIS OF TEACHER'S ABILITY IN APPLYING MIKIR ELEMENTS IN ACTIVE LEARNING AT HIGH CLASSES IN THE PRIMARY SCHOOL - Yantoro Yantoro (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The purpose of this research is to identify teacher’s ability in applying active learning with the elements of MIKIR (Experiencing, Interaction, Communication and Reflection). This research used desciptive qualitative approach. This research took place at Mendalo Elementary School 211 / IX. The subject of the research was the high class teacher (class IV, V and VI). Technique of collecting data was through observation, interviews and documentation. The data were analyzed through data reduction techniques, data display and data verification. The result showed that the high class teacher had applied the element of MIKIR in active learning. The ability of each teacher is different due to the vision and work ethic, the seriousness of the teacher in participating in active learning training applying the MIKIR element, the seriousness of the teacher in following up on the results of the training and mentoring conducted by the principal. This study concluded that teachers have done active learning by applying the MIKIR element, but the quality of implementation must be improved in order to develop student’s full potential.